Advances in intrahepatic and extrahepatic vascular dysregulations in cirrhotic portal hypertension - Li, Yanqiu; Zhu, Bingbing; Shi, Ke; Lu, Yu; Zeng, Xuanwei; Li, Yongqi; Zhang, Qun; Feng, Ying; Wang, Xianbo (Frontiers in Medicine, 2025)
Cirrhotic portal hypertension, the most prevalent and clinically significant complication of liver cirrhosis, manifests as elevated portal venous pressure and is associated with severe complications. Although much research on the mechanisms of portal hypertension has focused on liver fibrosis, less attention has been given to the role of intrahepatic and extrahepatic vascular dysfunction, particularly with respect to extrahepatic vasculature. While the role of hepatic fibrosis in cirrhotic portal hypertension is undeniable, the underlying mechanisms involving intrahepatic and extrahepatic vasculature are highly complex. Sinusoidal capillarization and endothelial dysfunction contribute to increased intrahepatic vascular resistance. Hemodynamic changes in the extrahepatic circulation, including splanchnic vasodilation and hyperdynamic circulation, play a significant role in the development of portal hypertension. Additionally, therapeutic strategies targeting these vascular mechanisms are diverse, including improvement of sinusoidal microcirculation, therapies targeting hepatic stellate cells activation, and pharmacological modulation of systemic vascular tone. Therefore, in this review, we will discuss the vascular-related mechanisms and treatment progress of portal hypertension in cirrhosis to provide a new theoretical basis and practical guidance for clinical treatment.